The Livelihood of Adult Daughters According to Islamic Law: A Case Study of Students at the Syekh Abdul Halim Hasan Institute - Rangkuti, Ahmad Zuhri (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
see the Orignal Version in Pdf